2016
DOI: 10.1080/00206814.2016.1193773
|View full text |Cite
|
Sign up to set email alerts
|

Identifying late Carboniferous sanukitoids in Hala’alate Mountain, Northwest China: new constraint on the closing time of remnant ocean basin in West Junggar

Abstract: Volcanic rocks in the Hala'alate and Aladeyikesai formations, which are composed of basaltic andesite and pyroxene andesite, are widespread in Hala'alate Mountain, West Junggar, Northwest China. These rocks (plagioclase + clinopyroxene/olivine) formed in the late Carboniferous and show a remarkable geochemical affinity with typical sanukitoids with oversaturated SiO 2 (52.9-56.9 wt.%) and high MgO (3.47-6.88 wt.%, Mg # >48) contents. They also exhibit a narrow range of Sr-Nd-Pb isotopes within ( 87 Sr/ 86 Sr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
(101 reference statements)
0
15
0
Order By: Relevance
“…Moreover, the Late Carboniferous–Early Permian mafic dikes, intermediate–felsic stocks, and basic volcanic rocks, which are located on both sides of the Darbut fault, were reported with typical features of sanukitoids in Setouchi volcanic belt of SW Japan ( ca . 322–291 Ma; Duan, Li, Zhi, & Wang, , in press; Li et al, ; Ma et al, ; Tang et al, ; Yin et al, , 2015). Additionally, the Late Carboniferous Hatu tholeiites ( ca .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the Late Carboniferous–Early Permian mafic dikes, intermediate–felsic stocks, and basic volcanic rocks, which are located on both sides of the Darbut fault, were reported with typical features of sanukitoids in Setouchi volcanic belt of SW Japan ( ca . 322–291 Ma; Duan, Li, Zhi, & Wang, , in press; Li et al, ; Ma et al, ; Tang et al, ; Yin et al, , 2015). Additionally, the Late Carboniferous Hatu tholeiites ( ca .…”
Section: Discussionmentioning
confidence: 99%
“…The first subduction–accretionary finished at the Early Carboniferous and then developed into intracontinental post‐collisional evolution. The second subduction–accretionary occurred in the southern West Junggar region at the Late Carboniferous to early Early Permian and formed sanukitoid arc volcanic rocks in Hala'alate Mountain (Li et al, ). Meanwhile, during the formation of granitic magma, dioritic intrusions/dikes showing geochemical affinity with adakites and sanukitoids intruded upward along the regional faults into Early Carboniferous and/or Middle Devonian strata (Duan et al, ; Duan, Li, Zhi, & Wang, , in press; Ma et al, ; Shen et al, ; Tang et al, , 2010; Yin et al, ; Yin et al, ; Yin et al, ; Zhang et al, and this study), and some have experienced strong magma mixing between mantle‐ and crustal‐derived melts during their ascent and emplacement (Chao et al, ; Kang, Li, Zhang, Zhang, & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the lithologies and deformation features of the Tarbagatay Complex, together with zircon ages, suggest an accretionary origin generally with a top-to-the-south tectonic vergence, suggesting a N-dipping subduction beneath the Zharma-Saur arc, likely started in the Late Devonian and lasted until the middle Permian. Li et al (2017a) report the geochemical and isotopic analyses of late Carboniferous volcanic rocks in the Hala'alate and Aladeyikesai formations, which are composed of basaltic andesite and pyroxene andesite and widespread in Hala'alate Mountain, West Junggar, NW China. The authors found that the Hala'alate Formation volcanic rocks are similar to the sanukitoids of Karamay, formed by partial melting of the mantle metasomatized by slab-derived adakitic melts.…”
Section: Introductionmentioning
confidence: 99%